Dating of 4th millennium BC pile-dwellings on Ljubljansko barje, Slovenia - Čufar, Katarina; Kromer, Bernd; Tolar, Tjaša; Velušček, Anton (Journal of archaeological science, 2010)
We present absolute dates of seven late Neolithic pile-dwellings on Ljubljansko barje, Slovenia. They were settled from ca. 3600 to 3332 (±10) and from 3160 to 3071 (±14) cal BC, as shown by investigations of wood using dendrochronology and radiocarbon wiggle-matching. We defined eleven periods of intensive tree felling (and building activities) and one major settlement gap (when no trees were felled) from 3332 to 3160 cal BC. A major settlement gap presumably also followed after 3071 cal BC (i.e., after the end date of the investigated sites). Our investigations included over 2500 pieces of wood, mainly from the piles on which the dwellings were built. Among important wooden artefacts were a wheel with axle (one of the oldest preserved wheels in the world) and two dugout canoes, all from the settlement phase from 3160 to 3100 cal BC. As shown by parallel studies, the economy in the sites was characterized by copper metallurgy, skilful wood processing and use, cultivation of domestic plants, gathering of wild plants, animal husbandry, hunting and fishing. The settlements were contemporaneous with a number of sites in the north of the Alps, the younger ones coincided with the lifetime of the Neolithic Iceman (Ötzi). Since Ljubljansko barje has a strategic position at the crossroads between western central and (south) eastern Europe the presented absolute dates provide a basis for their comparison with other dated contemporaneous sites (in the west), to revise the chronology of similar sites in the (south) east (which are not yet exactly dated), and to evaluate their interconnection and roles in cultural development in prehistory.
Gesehen am 21.07.2023